Keratan sulfate glycosaminoglycan from chicken egg white - Fu, Li (Glycobiology, 2016)
Keratan sulfate (KS) was isolated from chicken egg white in amounts corresponding to ∼0.06 wt% (dry weight). This KS had a weight-average molecular weight of ∼36–41 kDa with a polydispersity of ∼1.3. The primary repeating unit present in chicken egg white KS was →4) β-N-acetyl-6-O-sulfo-d-glucosamine (1 → 3) β-d-galactose (1→ with some 6-O-sulfo galactose residues present. This KS was somewhat resistant to depolymerization using keratanase 1 but could be depolymerized efficiently through the use of reactive oxygen species generated using copper (II) and hydrogen peroxide. Of particular interest was the presence of substantial amounts of 2,8- and 2,9-linked N-acetylneuraminic acid residues in the form of oligosialic acid terminating the non-reducing ends of the KS chains. Most of the KS appears to be N-linked to a protein core as evidenced by its sensitivity to PNGase F.